EFFECTS OF BIOLOGICALLY ACTIVE SUBSTANCES USED IN SOYBEAN SEED TREATMENT ON OIL, PROTEIN AND FIBRE CONTENT OF HARVESTED SEEDS - Prochzka, Pavel; TRANC, Premysl; PAZDER, Katerina; Å TRANC, Jaroslav; VOSTÅ˜EL, Jan (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
In 4-year trials, soybean seeds were treated with biologically active substances: Lignohumate B (a mixture of humic acids and fulvic acids), Lexin (a mixture of humic acids and fulvic acids enriched with auxins), brassinosteroid (a synthetic analog of natural epibrassinolide 24) and so-called â€œComplex seed treatmentâ€ (a mixture of a saturated solution of sucrose, Lexin, the fungicide Maxim XL 035 FS and adjuvant on the base of pinolene). After harvesting soybean seeds from the individual variants, they were analyzed for oil, protein and fibre contents. The results show that the most effective method was Complex seed treatmentâ€ which, compared to the untreated variant, significantly increased not only the yield but also the oil content of the seeds.